Pengaruh Sanksi, Sosialisasi dan Edukasi, Pelayanan Pajak, dan Pemeriksaan Pajak Terhadap Kepatuhan Pajak - Purwanto, Dhanang Dharmarendra Dwiki; Puspita, Ayu Fury (Ekuitas: Jurnal Pendidikan Ekonomi, 2024)
This study examines the factors influencing tax compliance among individual taxpayers in Indonesia and Malaysia, focusing on tax socialization and education, tax services, tax audits, and tax sanctions. The background issue is the low tax compliance rate in Indonesia, which affects the government's ability to fund development. This research employs a quantitative method, utilizing a survey distributed to individual taxpayers in Singosari, Malang, Indonesia, and Melaka, Malaysia. Data analysis was conducted using regression to identify the influence of independent variables on tax compliance. The findings reveal that tax socialization and education, as well as tax services, do not have a significant impact on tax compliance in both countries. These results suggest that the Theory of Planned Behavior may not be appropriate for these variables, and the Diffusion of Innovations theory might be more relevant. On the other hand, tax sanctions and audits are shown to have a significant effect in enhancing tax compliance. In conclusion, a more effective approach to improving tax compliance is by reinforcing the threat of sanctions and the intensity of tax audits.